Sport heritage in VR: Real tennis case study - Gaugne , Ronan; Barreau , Jean-Baptiste; Duc-Martin , Pierre; Esnault , Elen; Gouranton , Valérie (Frontiers in Virtual Reality, 2022)
Traditional Sports and Games (TSG) are as varied as human cultures. Preserving knowledge of these practices is essential as they are an expression of intangible cultural heritage as emphasized by UNESCO in 1989. With the increasing development of virtual reconstitutions in the domain of Cultural Heritage, and thank to advances in the production and 3D animation of virtual humans, interactive simulations and experiences of these activities have emerged to preserve this intangible heritage. We propose a methodological approach to design an immersive reconstitution of a TSG in Virtual Reality, with a formalization of the elements involved in such a reconstitution and we illustrate this approach with the example of Real Tennis. Real Tennis is a racket sport that has been played for centuries and is considered the ancestor of tennis. It was a very popular sport in Europe during the Renaissance period, practiced by every layer of the society. It is still practiced today in few courts in world, especially in France, United Kingdom, Australia and USA. It has been listed in the Inventory of Intangible Cultural Heritage in France since 2012.